1994
DOI: 10.1080/09553009414551551
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of UV-induced DNA Cleavage by Analogues of iodoHoechst 33258

Abstract: Following the earlier demonstration that iodo-Hoechst 33258 sensitizes DNA and cells to UVA, presumably mediated by formation of a carbon-centred radical on the ligand upon dehalogenation, three isomeric analogues of iodo-Hoechst 33258 have now been studied. The isomers differ in the location of the iodine atom in the phenyl ring of the ligand, relative to the site of attachment of the bibenzimidazole moiety, and are accordingly denoted ortho-, meta- and para-iodoHoechst. Comparison of the ligands with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Comparison of o-, m-and p-iodoHoechst with respect to DNA strand breakage in plasmid DNA indicated remarkable differences in photopotency [13]. The ortho isomer was found to be more efficient than the meta and para isomers [14,15]. Moreover, the photo-induced cytotoxicity by these analogues in K562 cells also displays similar results [16].…”
Section: Introductionsupporting
confidence: 52%
“…Comparison of o-, m-and p-iodoHoechst with respect to DNA strand breakage in plasmid DNA indicated remarkable differences in photopotency [13]. The ortho isomer was found to be more efficient than the meta and para isomers [14,15]. Moreover, the photo-induced cytotoxicity by these analogues in K562 cells also displays similar results [16].…”
Section: Introductionsupporting
confidence: 52%
“…Sensitization of DNA can be accomplished by incorporation of a halogenated thymidine analogue in combination with Hoechst (Limoli and Ward, 1993;Paull et al, 2000;Rogakou et al, 1999), by incorporation of halogenated Hoechst (Martin et al, 1994;Martin et al, 1990) or of halogenated thymidine analogues alone (Lukas et al, 2003;Tashiro et al, 2000). Halogenation is thought to be required for DSB induction.…”
Section: Laser-assisted Damaging Techniquesmentioning
confidence: 99%
“…Using laser pulses as short as 12.5 s, with relatively low laser power, allowed us to efficiently photo-reactivate DNA damage in live cell imaging experiments (Figure 5). Of note, while the 405 nm laser light can also be used to generate DNA damage, (85,86), the laser intensity used for efficient PR is more than 10-fold lower than the intensities required to induce DNA damage (74). Our results indicated that PR is rather specific for 405 nm laser, as PLs were not efficiently activated by the 488 nm laser at settings normally used for imaging GFP-tagged factors (Supplementary Figure S5C-H).…”
Section: Discussionmentioning
confidence: 99%